2023
DOI: 10.3390/v15081651
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of the Antiviral Properties of Pistachios and Zeaxanthin against HSV-1

Abstract: The search for alternative clinical treatments to fight resistance and find alternative antiviral treatments for the herpes simplex virus (HSV) is of great interest. Plants are rich sources of novel antiviral, pharmacologically active agents that provide several advantages, including reduced side effects, less resistance, low toxicity, and different mechanisms of action. In the present work, the antiviral activity of Californian natural raw (NRRE) and roasted unsalted (RURE) pistachio polyphenols-rich extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The antiviral functions of lutein have also been investigated in stable HBV-producing human hepatoblastoma HepG2 2.2.15 cells, where it efficiently suppressed the dose-dependent secretion of HBsAg and inhibited extracellular HBV DNA. We have recently reported that zeaxanthin, a dietary carotenoid that accumulates in the retina as a macular pigment, exhibits strong antiviral activity against herpes simplex virus 1 (HSV-1, CC50: 16.1 μM, EC50 4.08 μM, SI 3.96), affecting viral attachment and penetration as well as viral DNA synthesis ( Pennisi et al, 2023 ). An overview of the use of carotenoids as therapeutic strategies against emerging viral diseases, such as COVID-19, has recently been published ( Khalil et al, 2021 ).…”
Section: Antimicrobial and Antiviral Properties Of Pistachio Bioactivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral functions of lutein have also been investigated in stable HBV-producing human hepatoblastoma HepG2 2.2.15 cells, where it efficiently suppressed the dose-dependent secretion of HBsAg and inhibited extracellular HBV DNA. We have recently reported that zeaxanthin, a dietary carotenoid that accumulates in the retina as a macular pigment, exhibits strong antiviral activity against herpes simplex virus 1 (HSV-1, CC50: 16.1 μM, EC50 4.08 μM, SI 3.96), affecting viral attachment and penetration as well as viral DNA synthesis ( Pennisi et al, 2023 ). An overview of the use of carotenoids as therapeutic strategies against emerging viral diseases, such as COVID-19, has recently been published ( Khalil et al, 2021 ).…”
Section: Antimicrobial and Antiviral Properties Of Pistachio Bioactivesmentioning
confidence: 99%
“…This reduction was associated with a decrease in viral DNA synthesis, highlighting the extract’s inhibitory effects on HSV-1 replication ( Musarra-Pizzo et al, 2020 ). More recently, we have further investigated the mechanisms involved in the anti-HSV-1 effect exerted by pistachio extracts ( Figure 3 ): NRRE and roasted unsalted (RURE) pistachio polyphenols-rich extracts blocked virus binding on the cell surface, impaired viral DNA synthesis, and prevented the accumulation of viral proteins ( Pennisi et al, 2023 ). Indeed, by testing six compounds present in pistachio polyphenolic extracts (α, β, and δ tocopherol, β-carotene, luteolin, and zeaxanthin), we have demonstrated that zeaxanthin inhibited HSV-1 replication by affecting both viral internalization and replication.…”
Section: Antiviral Effect Of Pistachios and Mechanism Of Actionmentioning
confidence: 99%
“…WST-8/CCK8 tetrazolium salt is reduced by cellular dehydrogenases to form an orange formazan product that is soluble in a tissue culture medium. The formazan produced is directly proportional to the number of living and metabolically active cells and is measured via absorbance at 460 nm [30]. Therefore, VERO cells (2 × 10 4 cells/mL) were grown in 96-well microtiter plates at 37 • C in a 5% CO 2 incubator for 24 h. Then, they were exposed to serial dilutions of L7OG CY, FA, and RA for 72 h and incubated with CCK8 tetrazolium salt for 4 h at 37 • C in a CO 2 incubator.…”
Section: Viability Assaymentioning
confidence: 99%
“…The study found that zeaxanthin had a high antiviral effect, with a CC 50 value of 16.1 µM, an EC 50 value of 4.08 µM, and a selectivity index (SI) of 3.96. These antiviral effects were attributed to zeaxanthin's ability to suppress viral attachment, penetration, and DNA synthesis [120].…”
Section: Antiviral Activitymentioning
confidence: 99%